Spectral studies of phthalocyanines - Opilski, Zbigniew; Pustelny, Tadeusz Piotr; Ignac-Nowicka, Jolanta (Photonics Letters of Poland, 2019)
The paper presents the results of research of the optical properties of nickel-phthalocyanines (NiPc) in a wide spectrum range of optical radiation . Phthalocyanines belong to the group of organic semiconductors with a complicated molecular structure. Spectral characteristics of complex refractive index and optical transmission coefficient were determined. The tests were carried out in the range of wavelengths of optical radiation: 300-2500 nm. By means of Surface Plasmon Resonance (SPR) method, tests concerning the possibilities of using nickel phthalocyanines in gaseous sensors of nitrogen dioxide in atmospheres of air and nitrogen were carried out. Full Text: PDF References P. Górka, St. Kowalski, Investigation of air pollution, Ed. by SUT, Gliwice, Poland, 2000 CrossRef J. Ignac-Nowicka, T, Pustelny, Z. Opilski,E. Maciak,W. Jakubik, M. Urbanczyk, "Examination of thin films of phthalocyanineas in plasmon system for their application in NO2 sensors", Optical Engineering, 42 (10), 2978 (2003) CrossRef T. Pustelny J. Ignac-Nowicka, Z. Opilski, "Optical investigations on layered metalphthalocyanine nanostructures affected by NO2 applying the surface plasmon resonance method", Opt. Appl. 34(4), 563 (2004) DirectLink J. Homola, "Surface Plasmon Resonance Sensors for Detection of Chemical and Biological Species", Chemical Reviews, 108(2), 462 (2008) CrossRef E. Maciak, T. Pustelny, "An optical ammonia (NH3) gas sensing by means of Pd/CuPc interferometric nanostructures based on white light interferometry", Sensor and Actuators, B: Chemical 189, 230 (2013). CrossRef N.B. McKeown, "Phthalocyanine-containing polymers", Journal of Materials Chemistry, 10 (9), 1979 (2000) CrossRef T Pustelny, J. Ignac-Nowicka, B. Jarzabek, A. Burian, "Optical investigations concerning layered metalphthalocyanine nanostructures affected by NO2", Opt. Appl. 34(4), 551 (2004) DirectLink A. Rydosz, E. Maciak,K. Wincza,S. Gruszczynski, "Microwave-based sensors with phthalocyanine films for acetone, ethanol and methanol detection", Sensors and Actuators, B: Chemical. 237, 876 (2016) CrossRef T. Pustelny, J. Ignac-Nowicka, Z. Opilski, "Experimental investigation of thin metalphthalocyanine layers CuPc, PbPc, NiPc by plasmon resonance method to be applied in NO2-sensors", Opt. Appl. 34(2), 249 (2004) DirectLink W. Jakubik, M. Urbanczyk, E. Maciak, T. , "Surface acoustic wave hydrogen gas sensor based on layered structure of palladium/metal-free phthalocyanine", Bull. Pol. Acad. Sci.-Tech. Sci., 56(2), 133 (2008) <a class="file" href="http://journals.pan.pl/dlibra/publication/126921/edition/110745/content/surface-acoustic-wave-hydrogen-gas-sensor-based-on-layered-structure-of-palladium-metal-free-phthalocyanine-jakubik-w-p-urbanczyk-m-maciak-e-pustelny-t?language=pl" target="_parent"> DirectLink M. Piliaric, J. Homola, "SPR Sensor Instrumentation", Chemical Sensors and Biosensors, 4, 95 (2006) CrossRef